Talent identification and development - Richards, R. (1999)
Much of what we consider to be 'talent' is actually the degree to which each swimmer possesses certain physical, physiological, or mental attributes that may contribute to performance. Many of the physical characteristics of the swimmer are controlled by his/her genetic profile; that is, they are beyond anything the coach may do in the training program to change these characteristics. The mature height of a swimmer and other anatomical characteristics (these are commonly known as one's somatotype) are not easily altered. Therefore, many TID systems have focused on anthropometric variables. Studies of elite swimmers have been used to identify what general physical characteristics are common to successful (vs their less successful peers) swimming athletes. The general premise is that a swimmer's morphology influences the horizontal components of lift and drag and thereby affects the potential to generate optimal propulsion and to minimise resistance forces. The typical profile of elite swimmers features these general characteristics: · tall (i.e. greater than 'average' height), · 'wide' shoulder girdle and 'narrow' hip width (note: wide and narrow are relative terms, the respective ratio will determine if the relationship is favourable), · long arms (note: the arm-span taken from the extremities of the outstretched arms should be equal to, or greater than, one's standing height), · favourable ratio of long-bone development in the legs (note: this means that the leg-length is greater than trunk length), · large hands and feet. There are also some inter-stroke variations that have been reported in the literature. For example, male breaststrokers tend to be slightly 'heavier' in their body build and larger feet. Freestylers and Backstrokers tend to be the tallest and have the longest legs (i.e. relative to body size). However, the overall differences between elite swimmers in the various strokes is usually less than the differences between elite and non-elite swimmers. Body composition also appears to be a good descriptive characteristic of elite swimmers. As a rule, elite swimmers tend to have ectomorphic body types. That is, they are relatively lean (i.e. a low percentage of body mass is carried as fat tissue) when compared to the endomorphic body type. Muscularity would be described as 'lean muscled' rather than the 'heavy muscled' mesomorphic body type. The body shape is typically narrow and wide at the shoulder, tapering to a narrow waist (i.e. the torso tapers in a V-shape as viewed from the front). The amount of body fat is one factor that may be controlled. To a large extent, one's body fat can be reduced through good nutrition practices and adequate aerobic training loads. Muscularity is also subject to the type and amount of exercise performed. However, ectomorphs tend to retain a 'lean muscular' appearance without developing excessive muscle bulk. A second group of factors are related to one's neuro-muscular control, these are much harder to measure but are no less obvious than more 'physical' characteristics. Experienced coaches can easily recognise that some swimmers have a better 'feel' for the water than others. This is evidence of the differences in the ability of individuals to sense pressure on the propulsive surfaces of the arms and legs. Talented swimmers are the ones who are quick to make adjustments to their movement patterns to continually maximise the fluid pressure applied. Swimming is a sport that relies upon 'feel' (i.e. tactile sense) more than sight, sound, etc. The quality of sensory input also affects the swimmer's ability to maintain a body position that reduces drag. Finally, a 'talented swimmer' will possess a great sense of balance and body awareness in the water. The physiological characteristics that are advantageous in swimming will depend upon the type of event a swimmer intends to pursue (i.e. distance or sprint). Physiological factors are more susceptible to change as a result of the type and volume of training. Therefore, only the extremes on the physiological spectrum of endurance-explosive-power variables may be a useful guide to talent identification. In recent years Bill Sweetenham (Australian Swimming Inc., National Youth Coach) has advocated the use of 'recovery ability' as a measure of physiological talent identification. Both sprint and endurance athletes will have a certain ability to absorb and recover from physical activity to a point where they can repeat the activity. This is one's ability to 'recover'. Last, but by no means least, are the characteristics associated with one's psychological make-up. Like the technical aspects of performance, these characteristics are sometimes hard to assess by traditional methods (i.e. standard tests). Research has not clearly identified individual characteristics, but there are general traits that are worth considering when putting together a TID protocol. In general, successful swimmers have a well-balanced sense of 'self'. That is, they have a healthy self-concept and belief in their own ability. They are usually the type of person who displays great determination and concentration to stay with a task to completion.